The Effects of Solvent Ratio and Extraction Time on Physicochemical Characteristics of Stevia Leaf Liquid Extract Using Microwave Assisted Extraction Method - Asri - Widyasanti; Agnes Klarasitadewi; Sarifah Nurjanah (BPFP Faperta UNIB, 2022)
Stevia (Stevia rebaudiana Bertoni) is one of the natural sweeteners which contains low calories and can be used as a substitute for sugar. The objective of this study was to determine the effects of solid-solvent ratio and extraction time on the physicochemical characteristics of stevia leaf liquid extract using microwave-assisted extraction. The observed characteristics were yield of extraction, total soluble solids content, specific gravity, and color. The method used in this research was a laboratory experiment with descriptive analysis using 3 different extraction times, which were 4, 5 and 6 minutes. The solid-solvent ratio used in this study was 3 levels, which were 1:30; 1:35 and 1:40 (g/ml). The result of this study indicated that extraction variations with a solid-solvent ratio of 1:30 (gml) and extraction time of 6 minutes produced the best total soluble solid contents 2oBrix and the highest specific gravity namely 1.0068, meanwhile, extraction variations with the solid-solvent ratio of 1:40 (g/ml) and extraction time of 4 minutes produced the best yield of extraction 87.95%.